Increase Creativity And Imagination Children Through Learning Science, Technologic, Engineering, Art And Mathematic With Loose Parts Media - Nipriansyah, Nipriansyah; Sasongko, Rambat Nur; Kristiawan, Muhammad; Susanto, Edy; Arinal Hasanah, Putri Fatmawati (Universitas Islam Negeri Raden Intan Lampung, 2021)
The STEAM method is applied to early childhood to provide broader thinking power in problem solving. Penelitian aims to describe the learning STEAM (Science, Technological, Engineering, Art and Mathematic) with media loose parts that can enhance the creativity and imagination of children. The research method used is descriptive qualitative using observation, interviews and documentation. In data analysis techniques, researchers used qualitative analysis techniques using data reduction, data presentation, and drawing conclusions. The research was conducted in 4 meetings in group B with 12 children. The results showed that STEAM learning with losse parts media could increase children's creativity and imagination. This can be seen from the observation that was made 4 times, all children experienced good development when learning with losse parts media.learning STEAM with losse parts can be applied to earlyplay groups childhood education, both inand kindergarten. This research not only improvescreativity children'sbut also increases children's imagination, the loose parts media used are also unique and natural.